Socrates, ironist and moral philosopher - Vlastos, Gregory (Ithaca, N.Y. : Cornell University Press, 1991)
"The author shows us a Socrates who, though he has been long overshadowed by his successors Plato and Aristotle, represented the true turning point in Greek philosophy, religion and ethics. In his quest for the historical Socrates, the author focuses on Plato's earlier dialogues, setting the Socrates we find there in sharp contrast to the Socrates of later dialogues, in which he is used as a mouthpiece for Plato's own doctrines, many of them anti-Socratic in nature." [Back cover].
Socratic irony -- Socrates contra Socrates in Plato -- The evidence of Aristotle and Xenophon -- Elenchus and mathematics -- Does Socrates cheat? -- Socratic piety -- Socrates' rejection of retaliation -- Happiness and virtue in Socrates' moral theory -- Epilogue: Felix Socrates.
Includes bibliographical references (pages 308-319) and indexes.